THE POSITION OF HYOID BONE ON LATERAL CEPHALOGRAPHS IN VARIOUS VERTICAL FACIAL PATTERNS - Ghazala,; Shahab Adil,; Zafar Ul Islam,; Gulalai Jan,; Sana Riaz,; Lalina Taj, (Journal of Postgraduate Medical Institute, 2023)
Objective: To determine the position of hyoid bone on lateral cephalographs in various vertical facial patterns of orthodontic patients visiting Peshawar Dental College. Methodology: This descriptive study was conducted at Department of Orthodontics, Peshawar Dental College. A total of 75 patients (46% male and 54% female) fulfilling the inclusion criteria were included through non-probability purposive sampling technique. These patients were divided into three groups of 25 patients each on the basis of FMA and Y axis on lateral cephalographs. Six angular, seven horizontal and seven vertical linear measurements were measured to evaluate the position of hyoid bone with its associated structures in different facial heights. Results: One way ANOVA and post hoc Bonferroni tests showed a statistically significant difference between hypodivergent and hyperdivergent patterns for angular measurement H axis-MP (p=0.021*) and vertical linear measurement H-MP (p=0.025*). In horizontal linear measurements, H-Pog has shown a statistically significant difference (p=0.023*) between normo-divergent and hyperdivergent facial patterns. Conclusions: Hyoid bone is positioned more infero-anterior in hyperdivergent subjects and superior-posterior in hypodivergent cases. The hyoid bone is positioned anteriorly in hyperdivergent subjects.